Invisible losses. What a catastrophe does to forest owners' identity and trust in afforestation programmes. Issue 1 (1st October 2019) - Deuffic, Philippe; Ní Dhubháin, Áine
Abstract: In Ireland the political consensus to expand forest cover has not been really questioned for the last five decades, neither by policy‐makers nor by forest owners' representatives. However, in 2014, Irish private forest owners experienced for the first time in their life a catastrophic windstorm. A qualitative survey, conducted among the forest owners affected by the storm, shows that beyond the economic losses this disaster deeply shook their convictions about the real benefits of afforestation programmes. Using the theoretical concept of relational expectations, we show that Storm Darwin deconstructed a significant part of their identity as their status switched from audacious pioneer to forestry loser overnight. The political and socio‐economic structures outweighed the agency of individuals and their initial desire not to reforest. While the reconstitution scheme gave them the direction to follow, it reduced the risk of desertion. However, our study also shows that landowners may be a lot more cautious before signing up for afforestation programmes in the future.